2019
DOI: 10.1128/aac.02233-18
|View full text |Cite
|
Sign up to set email alerts
|

The Fungal Cyp51-Specific Inhibitor VT-1598 Demonstrates In Vitro and In Vivo Activity against Candida auris

Abstract: Candida aurisis an emerging pathogen associated with significant mortality and often multidrug resistance. VT-1598, a tetrazole-based fungal CYP51-specific inhibitor, was evaluatedin vitroandin vivoagainstC. auris. Susceptibility testing was performed against 100 clinical isolates ofC. aurisby broth microdilution. Neutropenic mice were infected intravenously withC. auris, and treatment began 24 h postinoculation with a vehicle control, oral VT-1598 (5, 15, and 50 mg/kg of body weight once daily), oral fluconaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 27 publications
(36 reference statements)
2
35
0
Order By: Relevance
“…In the current study, there was also a clear relationship between fungal burden and survival, as treated mice that survived to the day 21 endpoint had lower kidney and brain fungal burden compared to those that succumbed to infection. The survival and fungal burden results for the control, fluconazole, and caspofungin groups are consistent with those we have previously reported demonstrating the overall reproducibility of this model (13,14).…”
supporting
confidence: 90%
“…In the current study, there was also a clear relationship between fungal burden and survival, as treated mice that survived to the day 21 endpoint had lower kidney and brain fungal burden compared to those that succumbed to infection. The survival and fungal burden results for the control, fluconazole, and caspofungin groups are consistent with those we have previously reported demonstrating the overall reproducibility of this model (13,14).…”
supporting
confidence: 90%
“…In addition, the tetrazole VT-1598, which acts in a similar fashion to the triazoles by inhibiting the biosynthesis of ergosterol (41), has also demonstrated in vitro and in vivo activity against C. auris (42).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from the Centers for Disease Control and Prevention (Atlanta, GA) reported that 93% of investigated C. auris isolates were resistant to fluconazole, 35% were resistant to amphotericin B, and 7% were resistant to echinocandins when susceptibility tested according to Clinical and Laboratory Standards Institute (CLSI) methodology (11). New antifungal agents, including ibrexafungerp, fosmanogepix, and VT-1578, have displayed in vitro activity against C. auris (1,(12)(13)(14)(15). Although the in vitro activity of ibrexafungerp against C. auris has been investigated by the CLSI method M27-A3, MIC data obtained using the EUCAST methodology are scarce (16).…”
mentioning
confidence: 99%